Mycological, Aflatoxin and Heavy Metals Composition of Dried Fish from Idi-ape Markets in Ilorin, Nigeria - Folashade Moboluwaduro Ajimati; Sunday Awe; Sheriffdeen Issa Bale (UMYU Journal of Microbiology Research)
Fish is a cherished and highly sort after food that is widely eaten among many communities in Nigeria and the world at large, with good nutritional values. This study is aimed at evaluating the mycological flora, aflatoxin, proximate composition and heavy metals content in different dried fish samples. A total of three samples were used in this study which are; Salvetinus fortinacis, Heterotis niloticus and Malapterurus electricus. Aflatoxin detection in samples were carried out using High Performance Liquid Chromatography. The proximate analysis was carried out to determine the percentage nutritional value in each of the samples. Heavy metals detection was carried out using Atomic Absorption Spectrometer Buck scientific model 230. The result of the mycological evaluation revealed that the mean fungal count of all samples ranged from 1.5 ± 0.71 to 22.5 ± 4.95 (x102 CFU/g). With H. niloticus having the highest while M. electricus had the least. The proximate analysis results revealed percentage moisture of samples ranged from 4.382 ± 0.02 to 6.869± 0.009 (%) with H. niloticus having the highest and S. fortinacis having least value. Ash ranged from 3.518 ±0.18 to 4.424 ± 0.06 (%) with H. niloticus having the highest and S. fortinacis having the least. Percentage carbohydrate ranged from 14.179 ± 0.26 to 15.728 ± 0.33 (%) with H. niloticuss having the highest and S. fortinacis having the least. Calorific value ranged 1270.115 ± 1.12 to 1407.66 ± 1.87 (KJ/100g) with H. niloticus having the highest and S. fortinacis having the lowest. Percentage lipid ranged from 10.549 ± 0.08 to 14.293 ± 0.10(%) with H. niloticus having the highest and S. fortinacis having the least. Percentage Crude fibre ranged from 22.389 ± 0.19 to 29.310± 0.03 (%) with S. fortinacis having the highest and H. niloticus having the least. Percentage Protein ranged from 35.529 ± 0.00 to 38.062 ± 0.00(%) with S. fortinacis having the highest and M. electricus having the least. The presence of mycotoxin producing fungi in the different dried fish samples led to the presence of different Aflatoxins (known carcinogenic toxin) in the samples which is of a threat to human health.